Pembuatan Aplikasi Perjalanan Dinas Berbasis Web di Kesatuan Bisnis Mandiri (KBM) Ecotourism Perum Perhutani Divisi Regional Jawa Barat Dan Banten - Sabilla, Maisya; Mukaram; Putri, Ivon Sandya Sari (Ebiz Prima Nusa, 2022)
Kesatuan Bisnis Mandiri (KBM) Ecotourism was formed at May 4th 2009 to manage tourist attractions under Perum Perhutani, the Regional Division of West Java and Banten. Because of that, KBM Ecotourism requires employees and managers to monitor or directly supervise tourist attractions on a regular basis through business trips. Every trip requires a business trip warrant or SPPD approved by General Manager and made by HR staff. Beside SPPD, travel documents needed by employees are accountability sheets that contain details of travel expenses. Currently, business trip recording system at KBM Ecotourism uses Microsoft Excel. SPPD and accountability sheets are created by manually changing the existing templates. The calculation of business trip expenses are still done manually by HR staff. To overcome this problem, a better system is needed so that the management of business trip in KBM Ecotourism becomes more effective and efficient. Because of that, a business trip application web-based was created to manage business trip in KBM Ecotourism. This application made by waterfall software development method. The waterfall model consists of analysis, design, coding and testing. After the application has been made, it is tested by the staff. The results of the implementation show that this application is easy to use and the recording of business trip in the company becomes faster. Compared with the previous system, the information of business trip displayed was more detailed. Travel document template also doesn't need to be changed many times because it will be processed immediately by the system and ready to be downloaded.